Spherical Crystals of Moxifloxacin: To Improve Solubility, Dissolution Rate and Micromeritic Properties - Ganesan, V. (Asian Journal of Pharmaceutical Research and Development, 2013)
Moxifloxacin is a fourth-generation synthetic fluoroquinolone antibacterial agent having poor solubility, bioavailability and micromeritic properties.To improve these properties Agglomerated crystals of moxifloxacin were prepared by a spherical crystallization technique using the ammonia diffusion system (ADS). This technique makes it possible to agglomerate amphoteric drugs like moxifloxacin, which cannot be agglomerated by conventional procedures. When an ammonia-water solution of moxifloxacin is poured into an acetone dichloromethane mixture under agitation, a small amount of ammonia is liberated in the system. The ammonia-water solution plays a role both as a good solvent for moxifloxacin and as a bridging liquid, allowing the crystals’ collection to take place in one step. Agglomerates were evaluated for micromeritics properties, drug release, scanning electron microscopy, differential scanning calorimetry, infrared spectroscopy, X-ray diffraction and compressibility properties. The study revealed that Micromeritic Properties, Solubility and In vitro drug release rate is increased when compared with pure Moxifloxacin.The properties of agglomerates were good enough to adopt direct compression technology.